Japanese translation, cross-cultural adaption and multicentre validation of the Zurich chronic middle ear inventory (ZCMEI-21-Jap). Issue 1 (February 2019) - Bächinger, David; Takagi, Daiki; Yamada, Hiroyuki; Teraoka, Masato; Okada, Masahiro; Hyodo, Jun; Röösli, Christof; Huber, Alexander M.; Hato, Naohito
Abstract: Objective: In the assessment of chronic otitis media (COM) and its treatment, patient-reported outcomes are becoming increasingly important. The aim of the present study was to translate and validate the Zurich chronic middle ear inventory (ZCMEI-21) in Japanese in order to provide the first Japanese-language instrument for measuring health-related quality of life (HRQoL) in COM. Methods: The ZCMEI-21 was translated into Japanese according to published guidelines. In order to assess validity, the ZCMEI-21-Jap total score was compared to a question directly addressing HRQoL as well as the five-level version of the EQ-5D questionnaire, a generic measure of HRQoL. Results: Demographic data and validity were assessed in a total of 91 COM patients. The ZCMEI-21-Jap total and subscale scores were well comparable to those of the original validation study. Cronbach's α of the ZCMEI-21-Jap was 0.85, indicating an excellent internal consistency. The ZCMEI-21-Jap total score showed a strong correlation (r = 0.68, p < 0.0001) to the question directly addressing HRQoL and, as expected, only a moderate correlation to the EQ-5D scores (r = 0.49, p < 0.0001 for descriptive system score and r = 0.44, p < 0.0001 for VAS score). Conclusion: We successfully translated the ZCMEI-21 into Japanese and were able to obtain sufficient information during the validation process for the use of the ZCMEI-21-Jap to quantify HRQoL in patients with COM. With the current study, we aim to take a step forward towards an international standardization of reporting HRQoL in COM.